Zarys problematyki wyłączenia odpowiedzialności karnej sprawcy wypadku sportowego = Exclusion of criminal liability of sports participants for sport injuries - Cegliński, Paweł (Journal of Education, Health and Sport, 2015)
Cegliński Paweł. Zarys problematyki wyłączenia odpowiedzialności karnej sprawcy wypadku sportowego = Exclusion of criminal liability of sports participants for sport injuries. Journal of Education, Health and Sport. 2015;5(12):647-655. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44760 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A647-655 https://pbn.nauka.gov.pl/works/694775 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015. Cegliński Paweł. Zarys problematyki wyłączenia odpowiedzialności karnej sprawcy wypadku sportowego = Exclusion of criminal liability of sports participants for sport injuries. Quality in Sport. 2015;1(4):46-53. eISSN 2450-3118. The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.12.2015. Revised 25.12.2015. Accepted: 29.12.2015. Paweł Cegliński Uniwersytet Mikołaja Kopernika w Toruniu Zarys problematyki wyłączenia odpowiedzialności karnej sprawcy wypadku sportowego Exclusion of criminal liability of sports participants for sport injuries Streszczenie Niniejszy artykuł dotyczy jednego z wielu problemów prawa karnego, którym jest odpowiedzialność karna sprawcy wypadku sportowego. Wywód oparto na najpowszechniej aprobowanej w nauce i praktyce koncepcji kontratypu dozwolonego ryzyka sportowego. W badaniach posłużono się metodą studiowania i analizy polskiej literatury przedmiotu. Rozważania teoretyczne uzupełniono przykładami empirycznymi. Słowa kluczowe: wypadek sportowy, prawo karne, ryzyko sportowe, wyłączenie bezprawności kryminalnej Abstract This paper deals with one of the criminal law problems, which is criminal liability of sports participants for injuries occuring during the practice of a sport. This article aims to provide a brief summarization of the most important conception explaining this problem in Polish law – sport risk as a circumstance excluding criminal liability. The research is supported by the analysis of Polish literature. There are also some empirical examples involved. Keywords: sport injuries, criminal law, sport risk, exclusion of criminal liability